Analysis of Factors Related to Patient Loyalty During The Covid-19 Pandemic at The Ciasmara Health Center in 2021 - Diah Setyawati (Muhammadiyah International Public Health and Medicine Proceeding, 2021)
Since the Covid-19 pandemic occurred in March 2020 in Indonesia, many aspects of life have been affected, including health care facilities. This condition has changed people's lifestyles, community visits to health care facilities have decreased. Public interest in visiting public health service facilities has also decreased. One of the public health facilities that feel the impact is the Public Health Center. The purpose of this study was to determine the factors - factors associated with patient loyalty at the Public Health Center. This type of research is quantitative analytic with a cross-sectional approach, the types of statistical tests used are the Chi-square test and Logistic Regression test. The location of the research was at the Ciasmara Health Center, the time of the study was from January to July 2021. The number of samples was 120 respondents, the sampling technique was total sampling. The results of the univariate analysis showed that most of the respondents were not loyal to Public Health Center services, namely 51.7%. The results of the chi-square test showed that of the 7 independent variables studied, only 3 variables were significant on patient loyalty (p-value < 0.05), namely: attitude (0.021), service quality (0.034), and employee performance (0.024). While the variables of knowledge, economic level, distance from the house, and infrastructure are not significant because the p-value > 0.05. The results of the logistic regression test showed that the most dominant factor related to patient loyalty was employee performance. The quality of service and employee performance at the Public Health Center needs to be improved as long as it is through improving services and providing rewards and punishments for employees who perform well and poorly. Next, the patient's attitude needs to be improved through education and counseling carried out by the Public Health Center.